Impact of SARS-CoV-2 infection in the population on peritoneal dialysis. The Spanish experience : preliminary results. - Emilio Sanchez-Alvarez; Maria Auxiliadora Bajo Rubio; Vicente Paraíso Cuevas; Virginia López de la Manzanara; Rosario Llópez Carratala; Diego Rodríguez Puyol; Hernando Trujillo Cuéllar; Jesús Grande Villoria; Luz Maria Cuiña Barja (RDPLF, 2020)
The recent appearance of the SARS-CoV-2 pandemic has had a significant impact on the general population. Patients on renal replacement therapy (RRT) have not been unaware of this situation, and due to their characteristics, they are especially vulnerable. We present the results of the analysis of the COVID-19 Registry of the Spanish Society of Nephrology. This online registry began operating on March 18, 2020. It collects epidemiological variables, contagion and diagnosis data, signs and symptoms, treatments, and outcomes. Patients were diagnosed with SARS-CoV-2 infection based on the results of the PCR of the virus, carried out both in patients who had manifested compatible symptoms or had suspicious signs and in those who had undergone screening after contact with another patient. As of July 18, the registry had data on 1748 patients, from all the autonomous communities. The most represented form of RRT is in-center hemodialysis (HDC), followed by transplant patients. Only 55 (4%) were on peritoneal dialysis (PD). PD patients' symptoms are similar to those of the general population. A very high percentage (93%) required hospital admission, but none in intensive care units. The most used treatments were hydroxychloroquine, lopinavir-ritonavir, and steroids. Mortality is high and reaches 18%. Age and pneumonia were independently associated with the risk of death. We also found a beneficial effect of PD over HDC. As conclusions, SARS-CoV-2 infection already affects a significant number of Spanish patients on RRT, mainly those on HDC. The proportion of infected patients on PD is significantly lower. Hospitalization rates are very high, and mortality is high; age and the development of pneumonia are factors associated with mortality, while those on PD had lower mortality.